2004
DOI: 10.1159/000076355
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Knowledge of Famous People in Mild Cognitive Impairment and Progression to Alzheimer’s Disease

Abstract: Patients with dementia of Alzheimer’s type (DAT) show severe impairment in recognizing famous people. The aim of the current study was to investigate if this well-known memory impairment of famous faces is already present in the preclinical phase of DAT and if the famous faces test can help to differentiate patients with mild cognitive impairment (MCI) who progress to dementia and those who do not. We compared baseline performance in a task of famous face identification in a sample of 116 patients with subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
60
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 47 publications
10
60
0
6
Order By: Relevance
“…In fact, aMCI individuals have been found to be significantly more impaired at naming and providing information about photographs of famous faces and famous monuments than about common objects (Ahmed et al, 2008;Joubert et al, 2010;Clague et al, 2011). Moreover, some studies have shown that aMCI individuals whose semantic knowledge of famous persons was most impaired had a higher rate of conversion to AD relative to non-converters (Thompson et al, 2002;Estevez-Gonzalez et al, 2004). Therefore, results of the present study suggest that there is a genuine and widespread semantic impairment in LOAD patients.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…In fact, aMCI individuals have been found to be significantly more impaired at naming and providing information about photographs of famous faces and famous monuments than about common objects (Ahmed et al, 2008;Joubert et al, 2010;Clague et al, 2011). Moreover, some studies have shown that aMCI individuals whose semantic knowledge of famous persons was most impaired had a higher rate of conversion to AD relative to non-converters (Thompson et al, 2002;Estevez-Gonzalez et al, 2004). Therefore, results of the present study suggest that there is a genuine and widespread semantic impairment in LOAD patients.…”
Section: Discussionsupporting
confidence: 42%
“…Tests of famous person knowledge have been particularly useful in demonstrating semantic breakdown in AD but also in amnestic Mild cognitive impairment (aMCI) (Estevez-Gonzalez et al, 2004;Vogel et al, 2005;Joubert et al, 2008;Joubert et al, 2010;Barbeau et al, 2012;Brambati et al, 2012). In fact, aMCI individuals have been found to be significantly more impaired at naming and providing information about photographs of famous faces and famous monuments than about common objects (Ahmed et al, 2008;Joubert et al, 2010;Clague et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, deficits on semantic category fluency tasks occurred as early as 12 years before a diagnosis of AD was established in a population-based cohort of elderly individuals who were followed longitudinally (Amieva et al, 2008). Several studies have also shown that aMCI patients suffered from early breakdown of semantic knowledge of famous people, and that older patients who later on developed AD were initially more impaired at naming famous faces when compared to older adults who did not develop AD (Estevez-Gonzalez et al, 2004;Thompson, Graham, Patterson, Sahakian, & Hodges, 2002;Vogel, Gade, Stokholm, & Waldemar, 2005). In a recent study, aMCI and early AD patients were found to be similarly affected in terms of their Correspondence and reprint requests to: Carol Hudon, Centre de recherche Université Laval Robert-Giffard; 2601, ch.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have even suggested that impaired semantic processing of famous persons may contribute to identifying patients who present with an increased risk of developing AD in the following years. More specifically, longitudinal studies have shown that aMCI patients who later on converted to AD were initially more impaired at naming famous faces relative to non-converters (Estevez-Gonzalez et al, 2004;Thompson, et al, 2002;Vogel, Gade, Stokholm, & Waldemar, 2005).…”
mentioning
confidence: 99%